DESKRIPSI PEMNELAJARAN TEMATIK UNTUK PENGUATAN NILAI KARAKTER INTEGRITAS DI KELAS IV SD MUJAHIDIN PONTIANAK - Irfan Najib; Bistari Bistari; Kartono Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Abstrak : This script aims to describe the strengthening of character education in Primary school. Character education becomes an important part in the effort to overcome the social problems that often hit this nation. Character education becomes an alternative solution that is considered the most appropriate and needs to be applied in everyday life is no exception in primary school. Educational institutions or schools are seen as effective places in an effort to shape positive children besides the family. Strengthening character education is the process of formation, transmission, transformation and development of students' ability to think, behave, and behave according to Pancasila values. Character education in educational institutions has the function of selecting and sorting out Indonesian culture and foreign culture that is more civilized and honorable. As a manifestation of the National Movement of the Mental Revolution (GNRM) that is changing the pattern of thinking (mindset), attitude, and behave better, religious, nationalist, independent, mutual cooperation and high integrity we must cultivate through strengthening character education, especially in primary school so all students know, understand, and apply to all aspects of life whenever and wherever located. All that can be realized when all stakeholders are involved to oversee, run, supervise, and evaluate all these processes so that it becomes a positive culture in primary school.Keywords : Character Education, Description, Primary School